Hydrogen Permeation Behavior of Carbon Steel During Corrosion in Highly Pressed Saturated Bentonite - Zhang, Qichao; Jiang, Yishan; Zhao, Xin; Song, Penglei; Kuang, Tingting; Chen, Juna; Sun, Zhongtao; Zhang, Yaopeng; Ai, Xiayu; Lu, Dongzhu; Huang, Yanliang (Frontiers in Materials, 2022)
Deep geological disposal is the most reliable method for high-level nuclear waste, of which metal container as the first barrier for deep geological disposal of high-level nuclear waste is particularly important. Carbon steel is used as a container material because of the low possibility of local corrosion in bentonite. However, after the storage is closed, the decrease of oxygen content will create a near-field environment where the hydrogen embrittlement (HE) in the corrosion process of the container could happen. To evaluate the safety of containers in deep geological disposal of Beshai, the preselected area in China, hydrogen permeation efficiency and HE were estimated in highly pressed saturated bentonite by electrochemical and extrapolation analyses. It is concluded that hydrogen permeation efficiency increases with the disposal year, which proves that the hydrogen evolution reaction dominates the cathode process in the corrosion during long-term disposal. However, slow strain rate tensile shows that Q235 steel has a low HE sensitivity.